Military expenditure in a free market economy - Helmut Schmidt (Intereconomics, 1968)
We put a number oJ relevant questions on the influence exerted by financing, procurement, and planning of military supplies on the general business climate, the growth, and the technical development to Helmut Schmidt, Chairman of the Social Democratic Parliamentary Party in the Bundestag at Bonn.
Keywords: 330; Interview